Autonomia dos pequenos municípios e a (in)suficiência da arrecadação tributária própria: Recorte com os pequenos municípios da Microrregião de Araxá - Santos, Marcio Pedrosa dos (2024)
The constituent legislator gave the municipalities absolute autonomy regarding the exercise of institution and collection of taxes assigned to them, subject only to the reservations contained in the Greater Text itself. However, the interpenetration of standards has acted unfavorably on municipalities, from the tax typology intended for them, to the implementation conditions. Thus, it is clearly inferred that the survival of municipalities (especially small ones) is compromised, given their insignificant own revenue, compared to that of other entities, and the dependence on transfers from superior entities that originate from there. This raises the question of the circumstances and challenges of the Brazilian tax distribution, in particular the sufficiency (or insufficiency) of municipalities' own tax collection, for the implementation of public policies that are able to serve their citizens. The research problem was, therefore, whether small municipalities are able to collect, on their own, taxes in an amount sufficient to implement the public policies entrusted to them; or if they depend on transfers from other entities for this, and maintenance of their basic structure, limiting themselves to administrative activity. The research hypothesis was that the constitutional divisions of tax jurisdiction harm the autonomy of small municipalities, given the limited revenue collected in them and the consequent financial dependence on transfers from other federated entities. The general objective was to compare the compatibility between municipal tax powers established within the framework of constitutional distribution and the powers, duties and role of municipalities in the development of public policies. The specific objectives were: to analyze cooperative federalism, implementation of public policies to be implemented, and the role of municipalities within Brazilian federalism and in the implementation of public policies; discuss procedures relating to the exercise of tax jurisdiction in the Brazilian scenario, proposing a discussion about the existence and effectiveness of municipal autonomy provided for in the Constitution; and materialize the theoretical considerations raised based on practical examples. Based on the illustration used, referring to small-sized municipalities in the Araxá micro-region, the constitutional divisions of tax jurisdiction can harm the autonomy of small-sized municipalities, given the limited revenue collected in them and the consequent financial dependence on transfers from other municipalities. federated entities to carry out their expenses, according to the research hypothesis initially suggested. Thus, although constitutional autonomy has been established in favor of the municipalities, the political-administrative decentralization that would enable effective autonomy has not yet achieved its maximum objectives.